Statins and Inflammation: New Therapeutic Opportunities in Psychiatry - Kim, Sung-Wan; Kang, Hee-Ju; Jhon, Min; Kim, Ju-Wan; Lee, Ju-Yeon; Walker, Adam J.; Agustini, Bruno; Kim, Jae-Min; Berk, Michael (Frontiers in Psychiatry, 2019)
Statins, which are widely used to treat hypercholesterolemia, have anti-inflammatory and anti-oxidant effects. These are thought to be responsible for the potential effects of statins on various psychiatric disorders. In this study, we comprehensively review the literature to investigate the effects of statins on various psychiatric disorders including depression, schizophrenia, and dementia. In addition, we review adverse effects and drug interactions of statins to give clinically useful information guiding statin use in the psychiatric field. Statins seem useful in reducing depression, particularly in patients with physical disorders such as cardiovascular disease. In patients with schizophrenia, negative symptoms may be reduced by adjuvant statin therapy. Studies on cohorts at risk for dementia have generally shown protective effects of statins, while those on treatment for dementia show inconsistent results. In conclusion, statins used in combination with conventional psychotropic medications may be effective for various psychiatric disorders including depression, schizophrenia and dementia. Further study is required to determine optimal doses and duration of statin use for the treatment of psychiatric disorders.